Expression of Salivary Resistin may Indicate Progression in Oral Pre-Malignant Lesions - Shafaq Saeed Roghay PJMD; Hira Batool; Mervyn Hosein; Afifa Razi; Adnan Zubeiri; Saima Butt (ziauddin University, 2020)
Resistin is a pro-inflammatory cytokine, expressed by cells of the immune-inflammatory cells. Levels of this cytokine were significantly increased in premalignant oral lesion tissues. "The association between inflammation and tumorigenesis is well established and epithelial-to-mesenchymal transition (EMT) links these two processes. EMT is a reversible process during embryonic development and is involved in organ fibrosis, tissue regeneration, wound healing and cancer progression. EMT endows cancer cells with enhanced abilities for migration, invasion and resistance to chemotherapy". Resistin plays an important role in innate defense mechanisms. The immune-inflammatory response against microbes is caused by local tissue destruction, which is an attempt to wall off infection, and produces pro-inflammatory mediators such as Tumor Necrosis Factor (TNF) , Prostaglandin E2 (PGE2) and Interleukin IL 1, IL 6, etc. Resistin's role was strongly suggested in inflammation by TNF-, IL-1β, 6 and lipopolysaccharide, by increasing its expression in peripheral blood mononuclear cells. The process of inflammation may enable cancer cell to metastasize by encouraging mesenchymal properties and cancer cell stemness. The objective of this review was to assess potential early biomarkers of malignant transformation such as biomarkers that could assist in early diagnosis of individuals at high risk. The data was collected through a comprehensive search using the keywords, "Oral Pre-malignant Lesions, Resistin, Saliva, Tumorigenesis" from Medline and Google Scholar, from 2000 to 2019.